Alexy's Critique of Legal Positivism - Sieckmann, Jan-Reinard (The Cambridge Companion to Legal Positivism, 2021)
Sieckmann argues that the central claim of Robert Alexy’s criticism of legal positivism is that there is a necessary connection between morality and the content of law, and that the separation thesis is thus false. In his earlier writings Alexy adduced three distinct arguments in support of the connection thesis: the argument from injustice, the argument from principles, and the argument from the necessary claim of law to correctness. He later substituted for these a more general argument from the dual nature of law. Alexy situates his critique within the perspective of a participant, as distinguished from the perspective of an observer. Sieckmann maintains that Alexy changed the focus of the debate about legal positivism from an exclusive concern with questions of legal validity to a more general concern with questions of the nature of law by emphasising that in addition to the usual classifying connections between morality, on the one hand, and legal systems, acts and norms, on the other, there are also qualifying connections. Sieckmann concludes that Alexy showed legal positivism to be a not fully satisfactory theory of law for those adopting the participant’s perspective.
CRIS-Team WoS Importer:2022-07-08
Keywords: claim to correctness; connection thesis; criteria of identification (argument from injustice; argument from principles); dual nature thesis; Robert Alexy